Bioorganic Phase in Natural Food: An Overview - Roopan, S. Mohana; Madhumitha, G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The focus of this singular work is to discuss the role and importance of bioorganic phase in food products-providing the first major reference source for researchers looking to understand all aspects of the isolation, extraction and application of this major element in natural foods. From the identifying features to its applications through biotechnology and nanobiotechnology, this book covers all of the important aspects of bioorganic phase and points to future uses and methods. With chapters focusing on phase extraction and application, food product synthesis and nanoparticle application, Bioorganic Phase in Natural Food: An Overview covers both conventional and non-conventional approaches for the extraction of bioorganic phase from various food sources. Toxicity studies in nanoparticles are presented, and the vital role played by bioorganic phase toward nanoparticles synthesis is outlined in full. For any researcher looking for complete coverage of all main aspects of bioorganic phase in foods, this work provides a comprehensive and well-researched view of this important subject. .
Chapter1: An introduction and overview of food science in day today life -- Chapter2: Importance of Food Science and Technology- Way to Future -- Chapter3: Extraction of bioorganic phase from various food sources -- Chapter4: Conventional and Non-conventional approach towards the extraction of bioorganic phase -- Chapter5: Isolation and characterization of Bioorganic phase from food source -- Chapter6: Cardamom: A Multipurpose species in food and commercial needs -- Chapter7: Total synthesis of natural products existence in fruits and vegetables -- Chapter8: Phytochemical and Pharmacological Importance of Plant Secondary Metabolites in Modern Medicine -- Chapter9: Anti-diabetic effect of fruits on different animal model system -- Chapter10: Potential Applications of Nanotechnology in Agriculture: Current Status And Future Aspects -- Chapter11: Bio-synthesized nanoparticles as photo-catalysts for destruction or degradation of toxic species -- Chapter12: Toxicological Studies and Regulatory Aspects of Nano based Foods -- Chapter13: Halochromic Sensors for Monitoring Quality of Aqua Food -- Chapter14: Mechanism and Application of Nano Assisted Carrier Systems in Food -- Chapter15: Controlling of food borne pathogens by Nanoparticles.
Keywords: Food science; Chemistry, Organic; Food Science; Organic Chemistry